Common Themes in Teaching Reading for Understanding: Lessons From Three Projects. Issue 3 (5th August 2016) - Goldman, Susan R.; Snow, Catherine; Vaughn, Sharon
Abstract: This article reflects a metaview of the work of the three research projects funded through the Institute for Education Sciences under the Reading for Understanding competition that addressed middle‐grade through high school readers (grades 4–12). All three projects shared the assumption that instruction is necessary for successful reading to learn just as it is for learning to read. Through multiple studies conducted independently, the three projects arrived at common themes and features of productive instruction for reading for understanding with adolescent readers. These common themes are elaborated with instructional examples and include the following: (a) Students purposefully engage with multiple forms of texts and actively process them, (b) instructional routines incorporate social support for reading through a variety of participation structures, and (c) instruction supports new content learning by leveraging prior knowledge and emphasizing key constructs and vocabulary.